2023
DOI: 10.1093/aje/kwad116
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Strategies for Remotely Sampling Hard-to-Reach Populations: Assessing Phone Versus Internet Respondent-Driven Sampling Approaches Among Venezuelan Refugees and Migrants in Colombia

Abstract: It is challenging to quantitatively measure vulnerability and risk factors of refugees and migrants residing outside of formal settlement settings. For hard-to-reach populations without available sampling frames, researchers have increasingly turned to novel sampling and statistical methods, like respondent-driven sampling (RDS). ‘Standard’ RDS is typically conducted face-to-face at fixed sites. However, during the COVID-19 pandemic, face-to-face survey methods and recruitment approaches posed high potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…As found in previous studies involving migrant individuals [33][34][35][36], the hypothesis that Venezuelan migrants are connected in social networks and have ties with other migrants was confirmed. Networks in both cities developed quickly.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As found in previous studies involving migrant individuals [33][34][35][36], the hypothesis that Venezuelan migrants are connected in social networks and have ties with other migrants was confirmed. Networks in both cities developed quickly.…”
Section: Discussionsupporting
confidence: 77%
“…Using traditional sampling methods, very large samples would be needed to gather a sufficient number of migrants to make it possible to estimate reproductive health indicators, disaggregated by variables of interest, such as age, educational level and place of residence, which would not be feasible due to operational difficulties and costs [ 37 , 38 ]. During the COVID-19 pandemic, a survey implemented RDS strategies to assess the challenges faced by Venezuelan refugees, and the methodology was suitable at sites where the sample size was reached [ 36 ]. A study that collected health information from Syrians who had migrated to Germany concluded that the RDS method was more appropriate and had a much higher response rate than that achieved by random sampling of population records [ 34 ].…”
Section: Discussionmentioning
confidence: 99%